Effects of paroxetine, ketoconazole, and rifampin on the metabolism of eliglustat, an oral substrate reduction therapy for Gaucher disease type 1 - Vu, Lucie (Mol Genet Metab Rep, 2020)
Eliglustat is an oral glucosylceramide synthase inhibitor indicated for the long-term treatment of adults with Gaucher disease type 1 and CYP2D6 extensive, intermediate, or poor metabolizer phenotypes. Eliglustat is metabolized primarily by CYP2D6 and to a lesser extent by CYP3A4 and is a substrate of P-glycoprotein (P-gp). Three studies evaluated the effects of paroxetine (strong CYP2D6 inhibitor), ketoconazole (strong CYP3A4 and P-gp inhibitor), and rifampin (strong CYP3A4/P-gp inducer; OATP inhibitor) on the pharmacokinetics of orally administered eliglustat in healthy adults. An 8.9-fold increase in eliglustat exposure following co-administration of multiple-dose eliglustat and paroxetine is attributed to inhibition of CYP2D6-mediated metabolism of eliglustat by paroxetine. A 4.3-fold increase in eliglustat exposure following co-administration of multiple-dose eliglustat and ketoconazole is attributed to inhibition of CYP3A4-mediated metabolism and/or P-gp-mediated transport of eliglustat by ketoconazole. Co-administration of eliglustat with oral doses of rifampin reduced eliglustat exposure by >85% due to induction of CYP3A4/P-gp by rifampin, while a single intravenous dose of rifampin had no effect on eliglustat, confirming that eliglustat is not an OATP substrate. Depending on CYP2D6 metabolizer phenotype, co-administration of eliglustat with CYP2D6 and/or CYP3A inhibitors or CYP3A inducers may alter eliglustat exposure, warrant dosage adjustment or use with caution, or be contraindicated.